sEMG-based Control Strategy for a Hand Exoskeleton System - Secciani, Nicola; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book reports on the design and testing of an sEMG-based control strategy for a fully-wearable low-cost hand exoskeleton. It describes in detail the modifications carried out to the electronics of a previous prototype, covering in turn the implementation of an innovative sEMG classifier for predicting the wearer's motor intention and driving the exoskeleton accordingly. While similar classifier have been widely used for motor intention prediction, their application to wearable device control has been neglected so far. Thus, this book fills a gap in the literature providing readers with extensive information and a source of inspiration for the future design and control of medical and assistive devices.
Introduction -- Background: first-stage device -- The new control system -- Tests and results.
Keywords: Biomedical engineering; Robotics; User interfaces (Computer systems).; Human-computer interaction; Biomedical Devices and Instrumentation; Robotic Engineering; User Interfaces and Human Computer Interaction; Exoskeleton Device